2011
DOI: 10.1108/14636641111157805
|View full text |Cite
|
Sign up to set email alerts
|

Good Lives sexual offender treatment for mentally disordered offenders

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/ authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…In this way, client autonomy is recognized through a collaborative approach to assessment. Clients with compromised intellectual functioning and/or a more complex and indirect GLM pathway to 15 offending might require additional support to develop an understanding of the links between their offending and the GLM (see Gannon et al, 2011).…”
Section: Y Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, client autonomy is recognized through a collaborative approach to assessment. Clients with compromised intellectual functioning and/or a more complex and indirect GLM pathway to 15 offending might require additional support to develop an understanding of the links between their offending and the GLM (see Gannon et al, 2011).…”
Section: Y Pmentioning
confidence: 99%
“…The GLM is complementary to the Risk, Need, Responsivity model (RNR; Andrews & Bonta, 2006;Bonta & Andrews, 2010), and preliminary empirical research suggests that the GLM can enhance RNR-based approaches, especially in terms of improving client engagement in treatment (e.g., Gannon, King, Miles, Lockerbie, & Willis, 2011;Simons, McCullar, & Tyler, 2006). In brief, the GLM can accommodate the major RNR principles within a broader strength-based framework (see Ward, Yates, & Willis, 2012).…”
mentioning
confidence: 99%
“…Various role-play techniques may be adopted by therapists according to the nature of the client group or individual in question. A common approach for instigating cognitive change revolves around requesting the client to write a hypothetical letter to their victim (Beckett, 1994;Gannon et al, 2011) or switch between playing themselves and their victim in a dual person role play (Mann et al, 2002;Stinson & Becker, 2013;Webster, Bowers, Mann, & Marshall, 2002). It can also be helpful to ask offending clients to act as 'self' and 'other' in new hypothetical interactions in order to aid them to understand how their beliefs, attitudes, and behaviors may be experienced by others.…”
Section: Role Play and Behavioral Rehearsalmentioning
confidence: 99%
“…In another example, Gannon et al (2011) reported preliminary findings from an evaluation of a Good Lives Sexual Offending Treatment Group (SOTG) in the United Kingdom, designed for males experiencing mental health difficulties. Using case study descriptions (n = 5), Gannon et al (2011) report that, despite their differential and complex needs, participants made progress during the program on some key indicators, including developing a more internalized locus of control.…”
Section: Effectiveness Of Good Lives Model Approaches In Reorienting mentioning
confidence: 99%
“…In another example, Gannon et al (2011) reported preliminary findings from an evaluation of a Good Lives Sexual Offending Treatment Group (SOTG) in the United Kingdom, designed for males experiencing mental health difficulties. Using case study descriptions (n = 5), Gannon et al (2011) report that, despite their differential and complex needs, participants made progress during the program on some key indicators, including developing a more internalized locus of control. Although all individuals had locus of control scores within the normal range pre treatment, in four out of the five case descriptions, issues related to autonomy were associated with their offending, and in one case description, the individual clearly identified an external locus of control, describing himself as having "little control" over his index offense (p. 163).…”
Section: Effectiveness Of Good Lives Model Approaches In Reorienting mentioning
confidence: 99%